ความพึงพอใจในการปฏิบัติงานของครูโรงเรียนเอกชน สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษานครราชสีมา เขต 4 - เจนเขว้า เสวียน; วงษ์อินทร์ ทองหล่อ (Academic Journal Phranakhon Rajabhat University, 2017)
The objectives of this research were 1) to study the job satisfaction of private school teacher under Nakhonratchasima Primary Educational Service Area Office 4 2) to compare their job satisfaction by age and experience. The population were 744 private school teachers under Nakhonratchasima Primary Educational Service Area Office 4. The samples were 250 by applying Krejcie&Morgan table. They were selected by the stratified random sampling and simple random sampling technique. The instrument was questionnaire with the reliability of 0.941. Data were analyzed by percentage, arithmetic mean, standard deviation, one way analysis of variance and Scheffe’ method. The results revealed that Job satisfaction of private school teacher under Nakhonratchasima Primary Educational Service Area Office 4 overall was rated at a high level. When considered in each aspect found maximum every aspects, The sides were satisfied with the maximum level orderly with work itself, responsibility, relationships with workmate. The sides with minimum satisfied was wages. There was no significant difference among the personnel with different ages on job satisfaction in overall. When considered in each aspect, it was found that there was significant difference in the aspects of work achievement and relationships with boss at the level .05, but there was no significant difference in the other aspects. There was a significant difference among the personnel with different experience on job satisfaction in overall. When considered in each aspect, it was found that there was significant difference in the aspects of recognition, progression, policy and administration, Supervision and wages at the level .05, but there was no significant difference in the other aspects.